Acute compartment syndrome of the anterior thigh following quadriceps strain in a footballer. Issue 2 (23rd March 2004) - Burns, B J; Sproule, J; Smyth, H
Abstract : A rare case is presented of acute anterior compartment syndrome in the thigh of a footballer caused by an acute quadriceps strain, exacerbated by poor first aid and alcohol ingestion. Decompressive fasciotomy with subsequent split skin grafting of the wound defect resulted in a satisfactory outcome. The diagnosis requires a high index of suspicion lest it be overlooked with inevitably disastrous consequences.